Oxygen Reduction Activity and Interfacial Structures of La0.8Sr0.2CoO3 at Initial Electrochemical Process in an Alkaline Solution - Akira MATSUZAKI; Masaaki HIRAYAMA; Shouya OHGUCHI; Mamoru KOMO; Atsunori IKEZAWA; Kota SUZUKI; Kazuhisa TAMURA; Hajime ARAI; Ryoji KANNO (Electrochemistry, 2022)
Oxygen reduction and evolution reactions (ORR and OER, respectively) of perovskite-type La0.8Sr0.2CoO3 were characterized using two-dimensional model electrodes with different reaction planes (001), (110), and (111). Synthesized by pulsed laser deposition, these thin (30 nm) and flat (roughness < 1 nm) electrodes can reveal the reaction plane dependence of the ORR activity. From steady-state polarization measurements in KOH (aq.), the ORR activity was the highest on the (001) film during the first ORR/OER cycle, and it decreased significantly during the second cycle. In-situ synchrotron X-ray diffraction clarified crystal structure changes in the bulk and surface regions of La0.8Sr0.2CoO3, and these changes are associated with forming oxygen defects during the initial electrochemical process. Furthermore, the La0.8Sr0.2CoO3 surface partially decomposed upon reacting with the aqueous solution, as clarified by hard X-ray photoemission spectroscopy. Therefore, the interfacial structures formed in the electrochemical reaction field is important for enhancing ORR and OER activities.